CARA PERNAFASAN DAN GERAK TORSO DALAM TARI GOLEK MENAK YOGYAKARTA - Sarjiwo - (FBS UNY, 2007)
The way of breath taking and torso movement are the esthetic characteristic of Yogyakartan Golek Menak dance. This dance, which was created by Sri Sultan Hamengku Buwono IX, is a dance inspired by Golek Menak puppet played by a dalang (the puppet player). The dance movement became a reference of Golek Menak Dance. The movement characteristic of Golek Menak puppet taken by Golek Menak dance is unjal ambegan (a way of taking a breath). Every dancer has to master that movement to be applied in every movement activity. However, not every dancer can do it well because unjal ambegan must be followed by torso movement to emphasize the movement so that the dance becomes beautiful. Therefore, unjal ambegan is not only a way of breath taking but also two body activities interrelated, not able to be independent. Both are ways of breath taking involving torso movement. Key words: Golek Menak dance, unjal ambegan, torso movement